The Effect of Viral Marketing on Blackberry Messenger Applications on Customer Satisfaction Through Purchasing Decisions on University Students in Sidoarjo: Pengaruh Viral Marketing Pada Aplikasi Blackberry Messenger Terhadap Kepuasan Pelanggan Melalui Keputusan Pembelian Pada Mahasiswa Di Sidoarjo - Yulianto, Mochamad Rizal; Suhartono, Suhartono; Ronny, Ronny (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2018)
The purpose of this study is to examine the effect of viral marketing on Blackberry Messenger applications on customer satisfaction through purchasing decisions on university students in Sidoarjo. This research hypothesis states that viral marketing affect customer satisfaction through purchasing decisions. This research data was collected by questionnaires distributed to 180 respondents in several universities in Sidoarjo. From the data obtained then tested the validity test, reliability test and structure equation model analysis using the SmartPLS statistical application. The results of this study indicate that viral marketing on the Blackberry Messenger application have a significant positive effect on customer satisfaction through purchasing decisions on university students in Sidoarjo